The limits of nationalism - Gans, Chaim (Cambridge : Cambridge University Press, 2003)
This book examines cultural nationalism from a liberal perspective. Chaim Gans examines demands made in the name of cultural nationalism, such as the claim for national self-determination, historical rights to territories and demands for nationality-based priorities in immigration. He argues that only limited forms of these demands are acceptable.
Cover; Half-title; Title; Copyright; Dedication; Contents; Acknowledgements; Introduction; 1 Nationalist ideologies -- a normative typology; 2 The liberal foundations of cultural nationalism; 3 National self-determination; 4 Historical rights and homelands; 5 Nationalism and immigration; 6 Nationalism, particularism and cosmopolitanism; 7 Conclusion; Bibliography; Index.
Includes bibliographical references and index.
Print version record.
eBooks on EBSCOhost
Keywords: Nationalism; Liberalism; Free enterprise; Nationalisme; Libéralisme.; nationalism; liberalism; POLITICAL SCIENCE -- Political Ideologies -- Nationalism; Free enterprise; Liberalism; Nationalism; Electronic books; Electronic books